A 3 year analysis of the outcome of various types of management for unexplained infertility in Hospital USM (2010-2013) - W Adnan, W Fadhlina (2014)
INTRODUCTION: A 3 year analysis of the outcome of various types of management for Unexplained Infertility in Hospital USM (2010-2013) OBJECTIVE: To evaluate the outcome of patients diagnosed with Unexplained Infertility undergoing Expectant Management (EM) compared to Controlled Ovulation Hyperstimulation (COH) and Controlled Ovulation Hyperstimulation and Intrauterine Insemination (COH+IUI). The primary outcome is the pregnancy rate. The secondary outcomes are the ovarian response and the endometrial response among patients receiving stimulated cycles. Apart from that we have also assessed the risk of developing Ovarian Hyper-stimulation Syndrome (OHSS) and multiple pregnancy among these patients. STUDY DESIGN: This is a retrospective and prospective cohort study among women with unexplained infertility from 1st December 2010 until 30st November 2013, aged 18-44 years old undergoing their treatment at Hospital Universiti Sains Malaysia (HUSM). The subjects were recruited from the infertility clinic at HUSM. They were given EM, COH or COH+IUI. RESULTS: Total of 109 patients was enrolled in this study; 36 patients under EM, 36 patients under COH and 37 patients under COH+IUI. There were no significant statistical differences between the 3 treatment groups, in terms of the socio demographic and characteristics of unexplained infertility i.e. age, BMI, ethnicity, husband’s smoking status, type of infertility and duration of Infertility. (p-value > 0.05) There is a significant difference in terms of pregnancy rate between the 3 treatment groups (p-value = 0.00). In EM group, 17 patients (47.22%) managed to conceive within the 12 months of follow-up. In the COH group, 13 of them (36.1%) managed to conceive using this regime .In COH+IUI group 2 of them (5.4%) managed to conceive using this regime, 1 patient from using CC + IUI and another one from using recombinant FSH +IUI. For correlation between ovarian response and pregnancy rate, result showed that patients in COH group had higher pregnancy rate with even 1 dominant follicle (69.2%) While in the COH+IUI group, the pregnancy rate is similar in patients with 1 dominant follicle and 2 dominant follicles. As a whole, there is significant correlation between pregnancy rate and number of dominant follicles (p-value= 0.01) For correlation between endometrial receptivity and pregnancy rate, result showed that patients in COH group had higher pregnancy rate when the endometrial thickness is between 6-10mm (69.2%). In the COH+IUI group, there is no significant difference seen in terms of pregnancy rate in couples with ET 1-5mm and ET 6-10mm. As a whole, ET is not a significant predictor for pregnancy rate for stimulated cycles (p-value=0.55) There were no differences between COH and COH+IUI group in terms of risk of developing OHSS and rate of multiple pregnancies. CONCLUSION: Expectant management is comparable to COH and IUI in the management of unexplained infertility in terms of pregnancy rate.